An Analysis Of Code Mixing And Code Switching On Najwa Shihab Podcast “Susahnya Jadi Perempuan” (Catatan Najwa) - Situmorang, Korinthya Exaudia; Pasaribu, Tiara Kristina; Sembiring, Rony Arahta (ELT Worldwide: Journal of English Language Teaching, 2023)
This research focuses on analyze the occurrence of code-mixing and code-switching in Najwa Shihab's podcast episode entitled "Susahnya jadi Perempuan" (Catatan Najwa). The podcast episode discusses various challenges and experiences faced by women in society. This research aims to identify the types and how code-mixing and code-switching are used in the podcast. To achieve this, the authors used a qualitative descriptive method based on Muysken's theory and Poplack's theory.  The data were then categorized based on the types of code-mixing and code-switching, such as Insertion, Alternation, and Congruent Lexicalitation code-mixing as well as Inter-sentential switching, tag switching and Intra-sentential switching. The data obtained from this podcast amounted to 87 data. The results are as follows; there are 62 code mix data consisting of 46 (74%) insertion data, 10 (16%) alternation data, and 6 (10%) congruent lexicalization data. Furthermore, there were 25 code switching data found, which consisted of 9 (36%) inter-sentential switching data, 3 (12%) tag switching data, and 13 (52%) intra-sentential switching data. The authors found that the use of code-mixing and code-switching in this podcast was greatly influenced by the person, such as, the social environment of Najwa and her guest stars. A notable finding from the research is the evident influence of the speakers' social environment on their linguistic choices. Specifically, the interactions between Najwa and her guest stars, coupled with the thematic content of the episode, played a pivotal role in shaping the patterns of code-mixing and code-switching observed. This expanded research offers a deeper understanding of the dynamic interplay of languages in contemporary media formats, emphasizing the significance of sociolinguistic factors in shaping linguistic choices. The study not only contributes to the existing body of knowledge on code-mixing and code-switching but also underscores the importance of analyzing modern mediums to capture the evolving nature of linguistic practices.